Second Language Learners’ Competence of and Beliefs About Pragmatic Comprehension: Insights From the Chinese EFL Context - Yang, He (Frontiers in Psychology, 2022)
This mixed-methods study investigates second language (L2) learners’ ability to comprehend conversational implicatures. It also explores their beliefs about and intentions to develop this ability using Ajzen’s theory of planned behavior (TPB). A total of 498 freshmen from a public university in China participated in the study. Data were collected using a web-based test, stimulated recall tasks and semi-structured interviews. Results show that the participants differed in recognizing the intended meanings. Complicated factors account for the variations. In addition to the types of implicature, learners’ beliefs about developing pragmatic comprehension also influence their learning intention, and subsequent performance. These beliefs include learners’ multi-layered, complex attitudes towards the outcomes of pragmatic learning, perceived self-efficacy beliefs regarding language proficiency and L2 cultural knowledge, actual behavioral control over opportunities and resources for pragmatic learning, and perceptions of less social pressure on pragmatic learning. Understanding these beliefs can help to explain and predict learners’ pragmatic learning behavior.